1997
DOI: 10.1089/mdr.1997.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-ResistantSalmonella typhiFrom Two Outbreaks: Few Ribotypes and IS200Types Harbor Inc HI1 Plasmids

Abstract: To investigate factors that could be involved in the emergence of antibiotic resistant S. typhi, we characterized R plasmids and antibiotic resistant S. typhi strains from two outbreaks of typhoid in Peru and Chile. Differences in the Inc HI1 plasmids of Peruvian and Chilean strains were identified by conjugation and incompatibility studies and plasmid DNA characterization. Antibiotic-resistant S. typhi harboring Inc HI1 plasmids belonged to a reduced number of Pst1 and Cla1 ribotypes and IS200 types, in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Another study found similarities in PFGE patterns and plasmid profiles of MDRST isolates from Tajikistan and the Indian subcontinent, suggesting that the ciprofloxacin-resistant strains isolated in Tajikistan originated from the Indian subcontinent (7). Several studies have associated large conjugative plasmids with the presence of the MDR phenotype (2,5,9,13,14,26). Our data and those of others thus support the suggestion that multiple-drug resistance in S. enterica serotype Typhi is largely due to the clonal expansion of a limited number of strains that have acquired (presumably) plasmid-mediated drug resistance genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found similarities in PFGE patterns and plasmid profiles of MDRST isolates from Tajikistan and the Indian subcontinent, suggesting that the ciprofloxacin-resistant strains isolated in Tajikistan originated from the Indian subcontinent (7). Several studies have associated large conjugative plasmids with the presence of the MDR phenotype (2,5,9,13,14,26). Our data and those of others thus support the suggestion that multiple-drug resistance in S. enterica serotype Typhi is largely due to the clonal expansion of a limited number of strains that have acquired (presumably) plasmid-mediated drug resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of diversity among MDRST strains suggests that the MDR phenotype may provide a selective advantage that has allowed these strains to spread relatively unchanged. Alternatively, the lack of diversity may indicate that relatively few strains of S. enterica serotype Typhi are capable of receiving and maintaining conjugative resistance plasmids (5). Continued monitoring of MDRST PFGE patterns for the divergence of existing patterns and the emergence of new patterns many help clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Enterobacteriaceae are the potential host range of IncHI1 plasmids, most of them have been isolated solely from the genus Salmonella (Suzuki et al, 2010). In fact, IncHI plasmids account for a significant percentage of the multiple antibiotic resistance phenotypes in this genus (Fica et al, 1997). Plasmid R27 confers to its host resistance to tetracycline.…”
Section: Role Of Hha and Ydgt Proteins In Fitness Of S Typhimurium Hmentioning
confidence: 99%
“…1). IncHI plasmids are low-copy-number conjugative plasmids that encode multiple-antibiotic resistance in S. enterica serovar Typhi (14). Plasmids belonging to the IncHI group have been considered to play a relevant role in the persistence and reemergence of this pathogen (20).…”
mentioning
confidence: 99%